Pitfalls in the diagnosis of thyroid dysgenesis by thyroid ultrasonography and scintigraphy - (:unkn) unknown (BIOSCIENTIFICA LTD, 2012)
Objectives: We aimed to investigate the reliability of thyroid ultrasonography (US) and scintigraphy in determining the type of thyroid dysgenesis (TD). Methods: The study included 82 children (8.0 +/- 5.6 years) with a diagnosis of TD by thyroid scintigraphy with (99m)Tc and/or US. The patients were re-evaluated 6.0 +/- 5.1 years after the diagnosis. Thyroid US was performed in all cases, regardless of the previous US imaging. Scintigraphy images performed at the time of diagnoses (n=60) were re-evaluated during the study. Those who had no scintigraphy at the time of diagnosis (n=22) or had discordant findings with US (n=6) underwent a new scintigraphy. Results: Scintigraphies revealed no uptake in 37, ectopia in 35, and hypoplasia in 10 cases. The sensitivity vs specificity for US to detect athyreosis, ectopia, and hypoplasia at the time of initial diagnoses was 90.5 vs 47.8, 10 vs 100, and 100 vs 80.4% respectively. The sensitivity vs specificity for scintigraphy at the time of initial diagnoses was 96.2 vs 100, 92 vs 97.1, and 100 vs 96%, respectively, for each diagnosis. Re-scintigraphy at the time of the study led to a change in the initial diagnosis of 3/6 cases. Repeated US showed disappearance of previously reported hypoplastic thyroid tissues in eight patients. Conclusion: US alone could not differentiate ectopia and athyreosis, whereas scintigraphy alone is also prone to mistakes in newborns and young ages. Dual thyroid imaging is important for precise structural definition of TD.
Keywords: PRIMARY CONGENITAL HYPOTHYROIDISM; ULTRASOUND; CHILDREN; ABNORMALITIES; INFANTS; VOLUME; GLAND